Metaphorizing martial law constitutional authoritarianism in Marcos's rhetoric (1972-1985) - Navera, Gene Segarra (Philippine studies : historical and ethnographic viewpoints, 2018)
"This article discusses the metaphorical constructions of martial law that emerge from selected speeches and publications of Ferdinand Marcos from 1972 to 1985. Using a sociocognitive perspective informed by conceptual metaphor studies, the author surfaces conceptualizations that constitute a schema in which constitutional authoritarianism is central to national life and Marcos as an authoritarian is rendered a democrat. This schema had been sustained throughout Marcos's authoritarian rule and has become so embedded in Philippine political discourse that it gets to be invoked by political rhetors long after the fall of the Marcos dictatorship."